2015
DOI: 10.1007/s12020-015-0624-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing functions in patients with euthyroid Hashimoto’s thyroiditis

Abstract: Sensorineural hearing loss has been reported in various autoimmune diseases. The relationship between Hashimoto's thyroiditis (HT) and the auditory system has not been previously evaluated. In this study, we investigated the effect of euthyroid HT on the hearing ability of adult patients. The study included 30 patients with newly diagnosed euthyroid HT and 30 age- and gender-matched healthy controls. All subjects had a normal otoscopic examination and tympanometry, and they were negative for rheumatoid factor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
2
17
2
2
Order By: Relevance
“…Thyroid autoimmunity seems to affect the inner ear, particularly inducing hearing loss at lower frequencies [131]. …”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…Thyroid autoimmunity seems to affect the inner ear, particularly inducing hearing loss at lower frequencies [131]. …”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…These comorbid chronic systemic conditions are well known to be associated with hypoxemia and disturbances in microvascular circulation. These diseases are common with OSAS and they can be a cause of hearing loss on their own (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Although these abnormalities can occur as a direct consequence of hypothyroidism [1], it has been suggested that the circulating antithyroid autoantibodies can lead to T-cell mediated vestibulocochlear dysfunction. A review of the literature shows various case studies documenting the association of these two autoimmune entities [1215] which demonstrate the existence of a clear relationship between thyroid autoimmunity and the inner ear damage, regardless of thyroid function. Furthermore, it is postulated that the immune complexes precipitation in the inner ear with concomitant autoimmune inflammation may be the pathogenic mechanism shared with HT.…”
Section: Discussionmentioning
confidence: 99%